Flipbook-Based Nutrition Education: A Strategy to Improve Self-Efficacy for Stunting Prevention Among Pregnant Women During the First 1,000 Days of Life - Mesrida Simarmata; Indra Agussamad; Siti Nurmawan; Tetti Seriati Situmorang; Astaria Br Ginting; Srininta Srininta; Zahara Herani; Fahrunnisa Herawati (Media Publikasi Cendekia Indonesia, 2026)
Maternal self-efficacy is a critical determinant in the application of nutritional knowledge to prevent stunting during the first 1,000 days of life. Innovative educational tools are needed to bolster pregnant women's confidence in managing their nutritional needs. This study aimed to evaluate the effectiveness of a flipbook-based nutritional education intervention on pregnant women's self-efficacy in preventing stunting. This quantitative study employed a quasi-experimental design with a two-group pre-post test. A total of 40 pregnant women at the Medan Denai Health Center were selected using total sampling and randomly assigned into two groups: a treatment group (n=20) receiving flipbook-based education and a control group (n=20) receiving education without flipbooks. Self-efficacy was measured using a validated 15-item questionnaire. Data analysis was performed using the Wilcoxon and Mann-Whitney tests due to the non-normal distribution of the data. In the treatment group, self-efficacy scores significantly improved from a pre-test mean of 35.75 to a post-test mean of 51.05 (Wilcoxon test, p=0.000). The control group showed a minimal increase from 35.35 to 36.25 (Wilcoxon test, p=0.041). A comparison between the two groups revealed that the treatment group achieved a significantly higher mean rank (29.88) compared to the control group (11.13). The Mann-Whitney test confirmed a significant difference (p<0.001), indicating that the flipbook intervention was more effective in increasing maternal self-efficacy than conventional methods. Flipbook-based educational innovation is an effective and promising tool for enhancing the self-efficacy of pregnant women in practicing stunting prevention during the first 1,000 days of life.